MODULATORY EFFECT OF ALOE VERA LEAF EXTRACT AGAINST SULPHUR DIOXIDE INDUCED LIVER INJURY IN ALBINO RAT - MADHURI YADAV; ASHA AGARWAL; PREETI KUMARI (International Journal of Pharma and Bio Sciences, 2013)
The present study was carried out to evaluate the antioxidative effect of Aloe vera (A. vera) aqueous leaf extract on hepatotoxicity induced by SO2 inhalation in male albino rats. Hepatotoxicity was assessed by estimating the Serum Alkaline Phosphatase (ALP), Aspartate Aminotransferase (AST), Alanine Aminotransferase (ALT), Gamma Glutamyl Transferase (GGT) and histopathological changes in liver of rats. Experimental rats were exposed to 80ppm hrd-1, SO2 gas per day for 30 and 60 days. A significant increase in Serum ALP (P<0.001), AST (P<0.01), ALT (P<0.001), GGT (P<0.05) and histopathological changes include hepatocytes necrosis, degeneration of hepatocytes, centrilobular necrosis, ballooning degeneration and cellular debris have observed after SO2 exposure in comparison to control rats. A marked reduction in liver injury is reported after exposure with oral administration of A. vera leaf extract (200mgkg-1 body weight d-1) in comparison to SO2 exposed rats. Antioxidative and anti-inflammatory properties of A. vera shows potential to modulate the hepatocellular damage induced by SO2 gas in rats.